The comparative efficacy of brodalumab in patients with moderate-to-severe psoriasis: a systematic literature review and network meta-analysis. (18th August 2018) - Sawyer, Laura; Fotheringham, Iain; Wright, Emily; Yasmeen, Najeeda; Gibbons, Carl; Holmen Møller, Anders
Abstract: Purpose: To evaluate the relative efficacy of brodalumab compared with approved biologic therapies and apremilast for moderate-to-severe psoriasis. Methods: We searched MEDLINE, Embase, and Cochrane for randomized controlled trials reporting induction phase responses. The primary analysis examined the proportion of patients achieving Psoriasis Area Severity Index (PASI) 50, 75, 90, or 100 responses using a random-effects Bayesian multinomial likelihood model with probit link, with and without adjustment for variation in study-level placebo responses. Results: A total of 54 studies were included. Based on PASI 100 response, the most efficacious therapies were brodalumab 210 mg every two weeks (Q2W) and ixekizumab. Brodalumab 210 mg Q2W was significantly more efficacious than adalimumab, apremilast, brodalumab 140 mg Q2W, etanercept, infliximab, secukinumab, and ustekinumab. Results were consistent for PASI 50, 75, and 90 outcomes and all sensitivity analyses. Conclusions: Our findings are consistent with pivotal trials which indicate that high levels of complete clearance can be achieved with brodalumab. Based on existing evidence, induction-phase efficacy of brodalumab is similar to ixekizumab and superior to other approved therapies, including anti-TNFs, apremilast, secukinumab, and ustekinumab.